INFORMATION STRUCTURE OF THE INTEGRATED TRANSPORT SYSTEM WEBSITE (Perner's Contacts, 2011)
In addition to designing the proper areas of the integrated transport system and determination of tariff are required sufficient information for passengers. This can be done via message boards or leaflets, but frequently used form is web page. This paper deals with the design of web page structure in terms of the information required for passengers.
Keywords: Integrated Transport System; structure; website